Gambaran Fungsi Kognitif Pasien Pasca Stroke - Boletimi, Reinaldi O.; Kembuan, Mieke A. H. N.; Pertiwi, Junita M. (Medical Scope Journal, 2021)
Abstract: Stroke or brain attack occurs directly and its incidence is still very high until now. It is reported that two-thirds of stroke patients suffered from cognitive impairment leading to dementia within three months after stroke that can interfere with oneâ€™s daily activities if left untreated. This study was aimed to obtain the description of cognitive function in post-stroke patients. This was a literature review study using three databases, as follows: Goggle Scholar, Pubmed, and Clinical Key, and the keywords were cognitive impairment, cognitive decline, post-stroke, and MoCA. There were 10 literatures that met the inclusion and exclusion criteria. The results showed that many post-stroke patients showed cognitive function decline in the visuospatial/executive, memory, language, attention, and abstract domains. Cognitive impairment occured mostly in male patients, age 60 years and over, low education, ischemic stroke, left hemisphere lesion, with a history of hypertension. In conclusion, there is a relationship between post-stroke cognitive impairment and the location of lesion, age, and education level, albeit, there was no relationship between the cognitive impairment and gender as well as diabetes mellitus.Keywords: cognitive impairment, post-stroke, MoCAÂ Abstrak: Stroke menyerang otak secara langsung dengan angka kejadian yang masih sangat tinggi sampai saat ini. Dua pertiga pasien stroke dilaporkan mengalami gangguan fungsi kognitif yang berujung pada demensia dalam tiga bulan pasca stroke serta dapat mengganggu aktivitas sehari-hari bila dibiarkan. Penelitian ini bertujuan untuk mendapatkan gambaran fungsi kognitif pasien pasca stroke. Jenis penelitian ialah literature review, dengan pencarian literatur pada tiga database yaitu Goggle Scholar, Pubmed, dan Clinical Key. Kata kunci yang digunakan ialah penurunan fungsi kognitif, pasca stroke, dan MoCA. Hasil seleksi mendapatkan 10 literatur yang memenuhi kriteria inklusi dan eksklusi. Hasil penelitian menunjukkan bahwa pada pasien pasca stroke sering terjadi penurunan fungsi kognitif dengan domain visuospasial/eksekutif, memori, bahasa, atensi, dan abstrak yang paling sering terganggu. Penurunan fungsi kognitif banyak ditemukan pada pasien laki-laki, usia 60 tahun ke atas, jenjang pendidikan rendah, stroke iskemik, lesi hemisfer kiri, dengan riwayat hipertensi. Simpulan penelitian ini ialah adanya hubungan antara penurunan fungsi kognitif dengan lokasi lesi, usia, dan jenjang pendidikan namun tidak terdapat hubungan dengan jenis kelamin dan diabetes melitus.Kata kunci: gangguan kognitif, pasca stroke, MoCA